Trends in the incidence of intensive care unit invasive mechanical ventilation and subsequent 2‐year survival in very elderly New Zealanders. Issue 1 (January 2015) - Tripp, D. G.; Purdie, G.; Hicks, P.
Abstract Background The number of elderly in the general population is growing. There are therefore implications for the provision of intensive care unit (ICU) care to elderly patients. Aim Our aim was to determine the incidence of ICU invasive mechanical ventilation (IMV), long‐term outcomes of patients treated with IMV, and trends in these variables over a 10‐year period in New Zealand, with a focus on very elderly patients (aged 80 years and over). Methods Analysis of New Zealand public hospital discharge data from July 1999 to June 2010, with linked long‐term mortality data. Transfers or readmissions to different hospitals were linked using a national unique patient identifier. Results There were 58 003 patients treated with IMV in a New Zealand ICU. Of these patients, 6.6% were very elderly. Population rates of ICU IMV declined or were static over all age groups. The 2‐year mortality rate ranged from 15% in patients aged 16–39 years to 52% in the very elderly. The 2‐year mortality rates for the very elderly were highest for acute medical patients (78%), followed by acute surgical admissions (46%) and elective admissions (35%). The 2‐year mortality rate for all patients declined over the study period, and declined or was static for all age groups and admission types. In the very elderly, the standardised mortality ratio of patients surviving at 1 year who survived their second year after admission, compared with the age‐matched general population, was lower than all other age groups. Conclusion For very elderly patients over the period 1999–2009, the population rate of IMV was static and 2‐year mortality declined.